2023
DOI: 10.3390/molecules28041537
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Metal-Containing Formate Dehydrogenases Revisited: The Formation of Bicarbonate as Product Intermediate Provides Evidence for an Oxygen Atom Transfer Mechanism

Abstract: Mo/W-containing formate dehydrogenases (FDH) catalyzed the reversible oxidation of formate to carbon dioxide at their molybdenum or tungsten active sites. While in the reaction of formate oxidation, the product is CO2, which exits the active site via a hydrophobic channel; bicarbonate is formed as the first intermediate during the reaction at the active site. Other than what has been previously reported, bicarbonate is formed after an oxygen atom transfer reaction, transferring the oxygen from water to formate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(129 reference statements)
1
7
0
Order By: Relevance
“…12,13 At issue is whether CO 2 (eq 1) or HCO 3 − (eq 3) is the immediate product of enzymatic formate oxidation. 13,14 There are also structural studies that have revealed alternative active site structures to those shown in Figure 1 where dissociation of the protein ligand has occurred, at least under reducing conditions and dependent on the reductant. 15,16 Regardless of the specific chemical mechanism, the reversible catalytic oxidation of formate/reduction of CO 2 continues to receive the attention of researchers across diverse fields due to its relevance to global warming and also to future energy storage.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 At issue is whether CO 2 (eq 1) or HCO 3 − (eq 3) is the immediate product of enzymatic formate oxidation. 13,14 There are also structural studies that have revealed alternative active site structures to those shown in Figure 1 where dissociation of the protein ligand has occurred, at least under reducing conditions and dependent on the reductant. 15,16 Regardless of the specific chemical mechanism, the reversible catalytic oxidation of formate/reduction of CO 2 continues to receive the attention of researchers across diverse fields due to its relevance to global warming and also to future energy storage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The physiological function of all formate dehydrogenases is the two-electron oxidation of formate (HCOO – ) to carbon dioxide (CO 2 ) (eq ) using various electron acceptors including NAD(P) + , cytochromes, quinones, and Fe–S proteins to mention but a few. ,, It has emerged that most, if not all, formate dehydrogenases are in fact bidirectional and may catalyze the reverse reduction of CO 2 to HCOO – . , The preponderance of evidence is that the reaction occurs via hydride transfer from the C–H group of formate to form CO 2 directly , consistent with the earlier conclusion that CO 2 is the direct product of the reaction and that the reaction occurs without oxygen atom transfer. Still, mechanisms involving oxygen atom transfer have been proposed. , At issue is whether CO 2 (eq ) or HCO 3 – (eq ) is the immediate product of enzymatic formate oxidation. , There are also structural studies that have revealed alternative active site structures to those shown in Figure where dissociation of the protein ligand has occurred, at least under reducing conditions and dependent on the reductant. , Regardless of the specific chemical mechanism, the reversible catalytic oxidation of formate/reduction of CO 2 continues to receive the attention of researchers across diverse fields due to its relevance to global warming and also to future energy storage HCOO CO 2 + H + + 2 e CO 2 + H 2 O normalHCO 3 + H + …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first results clearly showed that after a reaction time of 10 s with 13 C-labeled formate, labelled 13 C 18 O 16 O was detected, demonstrating that the oxygen of H 2 18 O water is indeed inserted into the product, which is rather bicarbonate and not CO 2 . We showed that the enzyme-catalyzed reaction was much faster as compared to the secondary hydration of CO 2 under our experimental conditions [ 40 ]. In contrast, in the azide-inhibited reaction, which we performed as a control, we obtained the same results as reported by Khangulov, showing that azide interferes with the reaction and with product formation.…”
Section: The Mechanism Of Formate Dehydrogenase: Classical Oxygen Ato...mentioning
confidence: 99%
“…When 13 C-labelled thioformate was used in the NMR experiment with low azide concentrations, thiocarbonate was clearly detected as the first intermediate before COS abundance began to increase steadily. Here, thiocarbonate is detected instead of thiobicarbonate, based on the fact that thiobicarbonate is more acidic than bicarbonate, less stable at this pH and is, in fact, easily deprotonated [ 40 ]. This clearly confirmed the oxygen atom transfer with bicarbonate/thiocarbonate as first reaction intermediate of the reaction, which are released from the enzyme before CO 2 or COS are formed in the slower non-enzymatic secondary reaction outside the enzyme.…”
Section: The Mechanism Of Formate Dehydrogenase: Classical Oxygen Ato...mentioning
confidence: 99%